PRIVATE LABEL AND PRICE ON CUSTOMER SATISFACTION AND ITS IMPACT ON RETAIL INDUSTRY CUSTOMER LOYALTY - Malini, Helma (Talenta Publisher, 2024)
This study seeks to determine and provide empirical evidence regarding the impact of private label and price on customer satisfaction and its influence on customer loyalty at Alfamart. This research is a casually associative quantitative investigation. This study's population consisted of all Alfamart consumers who purchased private label products. The sampling technique employs a purposive sampling method that incorporates non-probability sampling of a total of 100 respondents using a questionnaire to collect data. The method of data analysis employed begins with descriptive analysis of research data, discussion of research instrument tests, classic assumption tests, path analysis (Path Analysis), and statistical testing of hypothesis results using version 25 of the SPSS data processing programmed. Private label has a significant effect on customer satisfaction, price has a significant effect on customer satisfaction, private label has no significant effect on customer loyalty, price has no significant effect on customer loyalty, customer satisfaction has a significant effect on customer loyalty, private label has a significant effect on customer loyalty via customer satisfaction, and price has a significant effect on customer loyalty.